KOMPENSASI, PENGEMBANGAN KARIER DAN MOTIVASI KERJA KARYAWAN (Studi Kasus Pada Karyawan PT Katamata) - Moody H. Manalu; Stephanie B. P. Simbolon (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
High work motivation owned by employees really helps to improve the company's performance. Therefore, its need a specific way to increase employee motivation. This study uses two independent variables, namely compensation and career development to increase employee motivation. The number of samples in this study were 52 respondents. By using a random sample. Based on the results of partial statistical testing, the independent variable, namely career development compensation, has an effect on employee work motivation. Likewise, simultaneously the two variables, namely compensation and career development, have an effect on employee work motivation.